A Study of Parking Characteristics in a Central Part of Basrah City - Abduljaleel Ahmed, Lamia (Journal of Engineering and Sustainable Development, 2009)
Most parking problems occur in central business district (CBD) areas where enough parking is not provided. When drivers enter these areas, they may suffer a problem of finding a parking space. The first stage of this research project focused on major parking characteristics in a selected part of Basrah CBD. The second stage is the development of a computer program to determine the shortage of spaces and number of decks in suggested multi-deck parking.The program is written in FORTRAN 90 language to facilitate the running of program on digital computer. The operation of the program was explained with the aid of flow charts. The Parking No.1 in this study was a case study. The output shows that the total number of shortage spaces equal to 335, one deck will give 60 spaces, and will need 6 decks to cover the shortage in city center. It is recommended to use the program as a tool for designing multi decks parking.